The Effect of Varicocelectomy on Semen Anaysis and Pregnancy in Infertile Males - Ercan Öğreden; Ural Oğuz; Abdullah Çırakoğlu; Erdal Benli̇; Erhan Demi̇relli̇; Orhan Yalçın (Acta Medica Alanya, 2018)
Aim: We aimed to investigate the effects of varicocelectomy on semen analysis and pregnancy in infertile men.     Patients and Methods: We retrospectively reviewed the medical records of patients underwent varicoselectomy between 2009 and 2014 in two referal hospitals, and 180 infertile patients with complete records were included.  All surgeries were performed by using a microscope or loop. The preoperative and postoperative sperm parameters and spontaneous pregnancy rates were evaluated.                                                                                Results: Mean age of the patients was 29.6 (17-46) years. 99 (55%) of the patients achieved spontaneous pregnancy after the surgery. 81 (45%) of the patients were guided to infertility polyclinics for assisted reproductive methods. When the sperm parameters were analyzed, the rate of the patients who had improved sperm concentrations were 22.7%; the rate of the patients who had improved sperm motility (a+b)  was 59.4%; the rate of the patients who had improved sperm morphology was 51.1 (p<0.05).                         Conclusion: Consisted to the existing literature, our study has demonstrated the positive effects of microscopic varicocelectomy on semen analysis and pregnancy rates.